1986
DOI: 10.1073/pnas.83.18.7109
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium in regulating the cyclic GMP cascade of phototransduction in retinal rods.

Abstract: Both cGMP and Ca2' appear to be involved in the process of phototransduction in vertebrate rods, but their precise roles have been the subject of debate. To investigate the role of Ca21 we have artificially increased the calcium buffering capacity of the rod by using a patch pipet to incorporate the calcium buffer 1,2-bis(o-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid (BAPTA) into the rod cytoplasm. In the presence of buffer the Na'-Ca2' exchange current became greatly slowed, suggesting that the cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
80
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 37 publications
14
80
1
Order By: Relevance
“…It is of some interest that the four flash responses in Fig dark level in Ringer solution, since previous experiments have shown that manipulations expected to elevate CaF+ lead to a lengthening of the duration of bright flash responses Matthews, Torre & Lamb, 1985;Hodgkin, McNaughton & Nunn, 1986;Torre et al 1986). Results similar to those in Fig.…”
Section: Role Of Calcium In Rod Light Adaptationsupporting
confidence: 76%
See 1 more Smart Citation
“…It is of some interest that the four flash responses in Fig dark level in Ringer solution, since previous experiments have shown that manipulations expected to elevate CaF+ lead to a lengthening of the duration of bright flash responses Matthews, Torre & Lamb, 1985;Hodgkin, McNaughton & Nunn, 1986;Torre et al 1986). Results similar to those in Fig.…”
Section: Role Of Calcium In Rod Light Adaptationsupporting
confidence: 76%
“…3B, we incorporated the calcium buffer BAPTA into the cytoplasm. The presence of buffer would be expected to slow any changes in Ca2+ and therefore to slow correspondingly the time course of current increase (see, for example, Lamb et al 1986;Torre et al 1986). Figure 3C shows the response in low-Ca2 , 0-Na+ solution (i.e.…”
Section: Lithiummentioning
confidence: 99%
“…Therefore, evolution, through the substitution of two amino acids (YG) in the filter of K + channels and the local modification of the amino-acid sequence of the interface between the voltage-sensing domain and the pore, has transformed a member of the family of voltage-gated channels into a non-voltage-gated channel, but only for Na + and K + . As a consequence of this substitution, CNG channels have also lost selectivity, allowing the permeation of Ca 2 + ions 13 and having a major role in the sensory adaptation in both photoreceptors and olfactory sensory neurons 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…One interpretation of the Fain et al result is that the steps cause a gain reduction early in the cascade, in the activation stages (e.g. Torre et al, 1986;Kawamura & Murakami, 1991;Pepperberg et al, 1994;Matthews, 1995;Fain et al, 2001). By this scheme, a saturating flash following a light-adapting step will simply not elicit as many PDE* as a dark-adapted flash, thus reducing T sat .…”
Section: On the Relative Roles Of Ca 2+ -Feedback At Early Versus Latmentioning
confidence: 99%
“…Nakatani & Yau, 1988;Forti et al, 1989;Tamura et al, 1991;Koutalos et al, 1995) and late in the recovery to bright flashes (e.g. Baylor et al, 1974;Torre et al, 1986;Pepperberg et al, 1992Pepperberg et al, ,1994.…”
Section: Limitations and Future Directions For Research And Model Devmentioning
confidence: 99%